Loss of CDS1 impairs the tumorigenic characteristics of nasopharyngeal carcinoma by modulating lipid metabolism - Yifang Wang; Limei Li; Liudmila Matskova; Lixian Deng; Danping Li; Yi Huang; Haili Liang; Wen Wang; Ziyuan Liang; Jiaming Su; Weilin Zhao; Tingting Huang; et al. (Cell Adhesion & Migration)
The accumulation of lipid droplets (LDs) enhancing nasopharyngeal carcinoma (NPC) cell migration. We reveals that CDP-diacylglycerol synthase 1 (CDS1), an inhibitor of LDs formation, is significantly downregulated in NPC. Restoring CDS1 expression suppresses NPC cell growth, colony formation, tumorigenesis, migration, and invasion. The anti-cancer effect of CDS1 is attributed to its role in decreasing the intracellular LDs. Moreover, CDS1 promotes activation of the NF-κB signaling pathway, resulting in elevated levels of inflammatory cytokines within NPC cells. This is likely to enhance the immunogenicity of these cells, thereby reducing tumor volume in the in vivo model. These findings establish CDS1 as a novel suppressor of NPC by modulating LDs levels, suggesting potential therapeutic avenues aimed at limiting LDs accumulation.